Experimental Investigation on the Axially Loaded Performance of Notched Hexagonal Concrete-Filled Steel Tube (CFST) Column - Jing Liu; Zhe Li; Fa-Xing Ding (Advances in Civil Engineering)
This study aimed to investigate the static performance of notched hexagonal concrete-filled steel tube (CFST) stub columns through axial loading. Notch length, notch location, and notch direction in 14 CFST stub columns were experimentally studied. Stress process, failure mechanism, and ultimate strength in the notched CFST columns were analyzed. Results show that notches in steel tubes can weaken the restraining effect of steel pipes on core concrete and induce a decrease in the ultimate strength of specimens. The failure mode of components is greatly affected by notch orientation. The notch is closed under axial compression in the horizontally notched specimen, and the slotting indicates outward buckling in the vertically notched specimen. Based on the test results, a method for calculating the ultimate strength of notched hexagonal CFST columns was established. This research encourages the extensive application of these structures in civil engineering.